The Social Network of the Holy Land - Christian Canu Højgaard (Religions, 2025)
The so-called Holiness Code (Leviticus 17–26) describes the land (אֶרֶץ) almost as a human being. In biblical scholarship on this law-text, the land has often been explained as an independent agent and more powerful than even the human beings that are present in the text. This paper will use social network analysis to test these conclusions and provide a more detailed account of the role of the land. The paper sets out to develop a social network model of the Holiness Code by including all interactions among human/divine participants and physical space. The paper then explores how human/divine participants relate to space, and it is shown that the participant roles are closely connected to access to space. Afterwards, the social role of the land is scrutinized by exploring each of its relationships, and by conducting a cluster analysis to understand the structural properties of the network. It is shown that the land is not as central and agentive as is usually thought but, rather, that the land plays a secondary role as a vulnerable character in need of protection. The paper is concluded by reflections on the potential of social network analysis for understanding character roles in literature.